Amber from México: Coahuilite, Simojovelite and Bacalite. Issue 1618 (2014) - Riquelme, Francisco; Ruvalcaba-Sil, José Luis; Alvarado-Ortega, Jesús; Estrada-Ruiz, Emilio; Galicia-Chávez, Martin; Porras-Múzquiz, Hector; Stojanoff, Vivian; Siddons, D. Peter; Miller, Lisa
ABSTRACT: Coahuilite, a new variety of amber is described from the Late Cretaceous Olmos Formation (ca. 73 Ma.), Coahuila, north of México. This amber is totally distinct chemically and stratigraphically from the Miocene Chiapas amber (ca. 23-13 Ma.), Southern México, which according to mineral nomenclature is currently known as Simojovelite var. nov. Additionally, an emended description of Bacalite is proposed, based on the physicochemical analysis and geological record of a fossil resin recently recovery from the Late Cretaceous El Gallo Formation (ca. 73 Ma.), Baja California, northwestern México. The results are supported by characterization of such ambers using synchrotron-based Infrared (FTIR) microspectroscopy.